ANALISIS PERBEDAAN BID-ASK SPREAD DAN ABNORMAL RETURN SAHAM SEBAGAI DAMPAK DARI PENGUMUMAN STOCK SPLITham Sebagai Dampak dari Pengumuman Stock Split - Janiantari, I Gusti Ayu; Badera, I Dewa Nyoman (E-Jurnal Akuntansi, 2014)
ABSTRACT This study examines the impact of the stock split announcement to the bid-ask spread and abnormal stock difference on the company listed in Indonesia Stock Exchange (IDX) 2008 through 2012. The study sample includes 28 companies using purposive sampling method. Data analysis technique used was Paired Samplet-Test for normally distributed data and Wilcoxon Signed Rank Test for unnormally distributed data. The analysis showed that there was significant difference between bid-ask spread before and after the stock split announcement. The same isindicated by the variable abnormal return.
Keywords: stock split, bid-ask spread, abnormal return